PENGARUH KUALITAS LAYANAN DAN HARGA TERHADAP LOYALITAS PELANGGAN DENGAN KEPUASAN SEBAGAI VARIABEL INTERVENING (STUDI PADA PELANGGAN XL PRABAYAR DI PAMEKASAN) - ROSA TAKHOLY, YENI (Jurnal Ilmu Manajemen (JIM), 2018)
Communication technology growing rapidly marked with the increasingly tight the competition among service provider industry. A tighter market condition drives the market players and producer to win the competition. This has led some providers to continually maintain the quality of service and pricing to maintain satisfaction and maintain customer loyalty. The tendency of consumers to change the mobile card also because some number of industry providers has decreased. The aim of this study is to analyze and explain the effect of service quality and price towards customer loyalty with satisfaction as intervening variable. Respondents in this study are respondents who bought and used Prepaid XL and constantly recharging pulse in minimum last 3 months. Respondent’s minimum 17 years old and the Prepaid XL which mentioned in this study are only for telephone. The study is done in PT. XL Axiata’s official distributor, PT. TEMA Pamekasan. Sampling technique used in this study is nonprobability sampling and sample is chosen by judgmental sampling with amount of 220 respondents. Data collection technique used in this study is a form of questionnaire. Measurement scales used is Likert scale. Data analysis technique is using Path Analysis with AMOS. The result of this study shows that there is a positive and significant influence between service quality and price towards satisfaction. There is a positive and significant influence between satisfaction and customer loyalty. There is a positive and significant influence between service quality and price towards. Keywords : Service Quality, Price, Satisfaction, Customer Loyalty.